MONITORING OF THE EFFICACY AND SAFETY OF HIGH-DOSE ATORVASTATIN IN ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION - L. I. Salyamova; S. S. Fadeeva; A. V. Golubeva; Yu. A. Tomashevskaya; V. E. Oleynikov (Рациональная фармакотерапия в кардиологии)
Aim. To study the effectiveness of achievement of lipid profile target levels and safety of therapy with atorvastatin in different doses in patients with acute ST-segment elevation myocardial infarction (STEMI).Material and methods. The open prospective controlled single-center study included 90 patients with STEMI aged 32 to 65 years. In the first 24-96 hours from the disease onset the patients were randomized into two groups: the first group included 43 patients who received high-dose statin therapy – atorvastatin 80 mg/day (Group 1), the second group (Group 2) – 47 patients receiving atorvastatin 20 mg/day. Examination of patients with STEMI included the assessment of plasma lipid profile, blood levels of hepatic transaminases, creatine phosphokinase (CPK), C-reactive protein (CRP), brain natriuretic peptide (BNP), creatinine, glucose and glomerular filtration rate calculation.Results. A decrease in the level of low density cholesterol (LDC) by 52.4% (p<0.001) was found after 24 weeks in Group 1. Achieving the target LDC level was found in 46% of patients and a decrease of LDC>50% from the baseline – in another 26%. LDC decreased by 33% in Group 2 (p<0.001). Achieving the target LDC level was found in 17% and a decrease of LDC>50% – in 15% of patients. After 24 weeks, a statistically significant decrease in hepatic transaminase activity was found in the both groups in comparison with the baseline level. The level of CRP decreased 9.1 times (p<0.001) in Group 1, and 7.8 times (p<0.001) – in Group 2. Reduction in the level of BNP was also found in Group 1 by 60% (p=0.005), and in Group 2 – by 33.8% (p<0.001). The levels of CPK, creatinine and GFR in the both groups did not change. A comparable decrease in fasting glycemia was found after 24 weeks in the both groups.Conclusion. The revealed lipid-lowering and pleiotropic effects confirm the necessity of using atorvastatin 80 mg. The absence of changes in the level of transaminases, CPK, serious adverse effects indicates the safety of the use of high-dose statin therapy in STEMI patients for the secondary prevention of cardiovascular events.